SGK1-FoxO1 Signaling Pathway Mediates Th17/Treg Imbalance and Target Organ Inflammation in Angiotensin II-Induced Hypertension - Du, Ya-Nan; Tang, Xiao-Feng; Xu, Lian; Chen, Wen-Dong; Gao, Ping-Jin; Han, Wei-Qing (Frontiers in Physiology, 2018)
It has been demonstrated that serum/glucocorticoid regulated kinase 1 (SGK1) and the downstream transcription factor forkhead box O1 (FoxO1) plays a critical role in the differentiation of T helper 17 cells/regulatory T cells (Th17/Treg). In the present study, we hypothesized that this SGK1-FoxO1 signaling pathway is involved in Th17/Treg imbalance and target organ damage in angiotensin II (AngII)-induced hypertensive mice. Results show that SGK1 inhibitor EMD638683 significantly reversed cardiac dysfunction in echocardiography and renal dysfunction as indicated by decreased serum creatinine and blood urine nitrogen in AngII-infused mice. Flowcytometric assay shows that there was significant Th17/Treg imbalance in spleen and in cardiac/renal infiltrating lymphocytes as indicated by the increased Th17 cells (CD4+-IL17A+ cells) and decreased Treg cells (CD4+-Foxp3+). Consistently, real-time PCR shows that Th17-related cytokines including IL-17A, IL-23 and tumor necrosis factor  (TNF-) was increased and Treg-related cytokine IL-10 was decreased in renal and cardiac infiltrating lymphocytes in AngII-infused mice. Meanwhile, SGK1 protein level, as well as its phosphorylation and activity, was significantly increased in spleen in AngII-infused rats. Furthermore, it was found that splenic phosphorylated FoxO1 was significantly increased, whereas total FoxO1 in nuclear preparation was significantly decreased in AngII-infused mice, suggesting that increased FoxO1 phosphorylation initiate its translocation from cytoplasm to nucleus. Notably, all changes were significantly inhibited by the treatment of EMD638683. These results suggest that SGK1 was involved in Th17/Treg imbalance and target organ damage in AngII-induced hypertension.